Development of a multiplex RT‐PCR for the detection of major diarrhoeal viruses in pig herds in China - Ding, Guangming (Transbound Emerg Dis, 2019)
The major enteric RNA viruses in pigs include porcine epidemic diarrhoea virus (PEDV), transmissible gastroenteritis virus (TGEV), porcine rotavirus A (PRV‐A), porcine kobuvirus (PKV), porcine sapovirus (PSaV) and porcine deltacoronavirus (PDCoV). For differential diagnosis, a multiplex RT‐PCR method was established on the basis of the N genes of TGEV, PEDV and PDCoV, the VP7 gene of PRV‐A, and the polyprotein genes of PKV and PSaV. This multiplex RT‐PCR could specifically detect TGEV, PEDV, PDCoV, PRV‐A, PKV and PSaV without cross‐reaction to any other major viruses circulating in Chinese pig farms. The limit of detection of this method was as low as 10(0)–10(1) ng cDNA of each virus. A total of 398 swine faecal samples collected from nine provinces of China between October 2015 and April 2017 were analysed by this established multiplex RT‐PCR. The results demonstrated that PDCoV (144/398), PSaV (114/398), PEDV (78/398) and PRV‐A (70/398) were the main pathogens, but TGEV was not found in the pig herds in China. In addition, dual infections, for example, PDCoV + PSaV, PDCoV + PRV‐A, PRA‐V + PSaV and PEDV + PDCoV, and triple infections, for example, PDCoV + PRV‐A + PSaV and PEDV + PDCoV + PKV, were found among the collected samples. The multiplex RT‐PCR provided a valuable tool for the differential diagnosis of swine enteric viruses circulating in Chinese pig farms and will facilitate the prevention and control of swine diarrhoea in China.